2019
DOI: 10.1002/ejoc.201900706
|View full text |Cite
|
Sign up to set email alerts
|

B(C6F5)3‐Catalyzed Reduction of Cyclic N‐Sulfonyl Ketimines

Abstract: A metal‐free method for reduction of cyclic N‐sulfonyl ketimines catalyzed by B(C6F5)3, using commercially available methylphenylsilane as a reducing reagent under mild conditions has been developed. This reductive protocol was effective, not only providing the expected cyclic N‐sulfonamides in good to excellent yields, but also showing good functional‐group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Compounds with a cyclic N-sulfonylamide fragment are of particular interest as they are often found in natural compounds, exhibit different biological activities, and can also be used as scaffolds for further modifications and synthesis of compounds for various purposes, for example, as ligands for asymmetric synthesis and chiral auxiliaries. [1][2][3][4] The presence of the endocyclic C=NSO2 fragment offers additional possibilities connected with the use of activated C=N bonds in cycloaddition 5 and addition reactions, 6,7 e.g., enantioselective preparation of biorelevant cyclic aminophosphonic acid derivatives. 7,8 Recent extensive studies of derivatives incorporating a 1,4,2-benzodithiazine-1,1-dioxide moiety have revealed among them anti-HIV agents, 9 potent KATP channel openers, 10 compounds with antitumor 11 and significant cytotoxic activities against ovarian (OVCAR-3) and breast (MDA-MB-468) cancers as well as a good selectivity toward prostate (DU-145), colon (SW-620) and renal (TK-10) cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with a cyclic N-sulfonylamide fragment are of particular interest as they are often found in natural compounds, exhibit different biological activities, and can also be used as scaffolds for further modifications and synthesis of compounds for various purposes, for example, as ligands for asymmetric synthesis and chiral auxiliaries. [1][2][3][4] The presence of the endocyclic C=NSO2 fragment offers additional possibilities connected with the use of activated C=N bonds in cycloaddition 5 and addition reactions, 6,7 e.g., enantioselective preparation of biorelevant cyclic aminophosphonic acid derivatives. 7,8 Recent extensive studies of derivatives incorporating a 1,4,2-benzodithiazine-1,1-dioxide moiety have revealed among them anti-HIV agents, 9 potent KATP channel openers, 10 compounds with antitumor 11 and significant cytotoxic activities against ovarian (OVCAR-3) and breast (MDA-MB-468) cancers as well as a good selectivity toward prostate (DU-145), colon (SW-620) and renal (TK-10) cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…N-Heterocycles, as important structural subunits, are frequently found in a wide range of natural products and biologically active pharmaceuticals. 1 Among them, compounds containing a cyclic N -sulfonamide moiety have versatile applications in biological molecules with therapeutic activities, such as HIV protease inhibitors, 2 potential modulators of neurotransmitters, 3 inhibitors of carbonic anhydrase, 4 and so on. 2 Over the past decades, a great deal of effort, including nucleophilic addition, 5 annulation reactions, 6 ring expansion, 7 and C–H functionalization 8 of cyclic sulfonyl ketimines, has been devoted to increasing the complexity of cyclic N -sulfonamides.…”
Section: Introductionmentioning
confidence: 99%